The Liturgical Year : Advent, Christmas, Epiphany (vol. 1) - Nocent, Adrien (Book collections on Project MUSE., 2013)
Adrien Nocent's The Liturgical Year was the first comprehensive commentary on the three-year lectionary in its relation to the Sacramentary of Paul VI. Now this extraordinary work of applied, postconciliar liturgical scholarship has been revised and annotated by Paul Turner. While taking care to keep Nocent's voice, the revision provides: a brief introduction, placing the commentary in its historical context; annotations that provide a bridge between Nocent's day and our own; explanatory notes on history, culture, language, and liturgy where needed; gender-inclusive language where appropriate; liturgical texts that conform to The Roman Missal, Third Edition. As we celebrate the fiftieth anniversary of Vatican II's Sacrosanctum Concilium, encounter again or for the first time the still fresh, vibrant scholarship and pastoral wisdom of Adrien Nocent's The Liturgical Year! (back cover).